Dangling Modifier on Students’ Final Projects - Mohammad Umar Fakhrudin; Pranata, Sudadi; Suwandi; Nurfitriyani, Vivi (EDUPEDIA Publisher, 2023)
This study aimed to identify, write corrections, and describe the impact of dangling modifier realized in the students’ final projects. The research design was descriptive qualitative by taking 30 final projects as the sample. To analyze the data collected, the writer employed data reduction, data display, and conclusion or verification. From 30 final projects analyzed, the writer found 18 final projects indicated dangling modifier. The most significant dangling modifier realized was dangling modifier begun with present participle. There are two ways to correct dangling modifier: by changing the subject of the sentence so that it goes with modifying phrase, or changing the dangling phrase into a subordinate clause by adding a subordinating conjunction and a subject. Dangling modifier affects readability and coherence of writing. The writer suggests the students to avoid common errors in writing, especially dangling modifier in order the writing will have good readability.